In Vitro Antioxidant Studies on Ethanolic Extracts of Leaf, Stem and Root of Sida Rhombifolia L. - NARENDHIRAKANNAN R.T; LIMMY T.P (International Journal of Pharma and Bio Sciences, 2010)
Antioxidant activity of the ethanol extract of Sida rhombifolia was determined by DPPH free radical, hydrogen peroxide scavenging assays, reducing power, total antioxidant capacity using phosphomolybdenum method, and rapid radical scavenging screening methods. Preliminary phytochemical screening revealed that the extract of S. rhombifolia leaves (SR-L), stem (SR-S) and roots (SR-R) possesses phenols, flavonoids, steroids, glycosides, saponins, tannins, and terpenoids. The extract showed significant activities in all antioxidant assays compared to the standard antioxidant (ascorbic acid) in a dose dependent manner and remarkable activities to scavenge reactive oxygen species (ROS) may be attributed by the presence of the above active compounds in SR-L, SR-S and SR-R.